PENERAPAN METODE MAMDANI DALAM PREDIKSI JUMLAH MAHASISWA BARU TEKNIK INFORMATIKA UNIVERSITAS MUHAMMADIYAH PAREPARE - Yunus, Ayuni; Yunus, Mughaffir; Masnur, Masnur (LPPM Universitas Putera Batam, 2025)
This study aims to apply the Mamdani-type Fuzzy Inference System (FIS) to predict the number of new students in the Informatics Engineering Study Program at Universitas Muhammadiyah Parepare. The main problem addressed is the annual fluctuation in student enrollment, which complicates capacity and resource planning. The data used includes historical admission records and questionnaire results from 30 respondents, consisting of lecturers, administrative staff, and program management representatives. The analysis focused on three aspects: ease of use, security and reliability, and user satisfaction and benefits of the application. The results indicate that the Mamdani-based prediction application achieved high accuracy and received positive responses from users. The average agreement rate for ease of use was 90%, security and reliability 87%, and satisfaction and benefits 88%. The strength of the Mamdani method lies in its ability to handle linguistic input variables and uncertainty, providing adaptive and relevant prediction results. However, further development is recommended for the automatic backup feature and result verification mechanisms to enhance data security. Overall, the implementation of the Mamdani method for predicting new student enrollment has proven to be practically beneficial for study program management and provides a theoretical contribution to the application of fuzzy logic in higher education. This research can serve as a foundation for developing more advanced predictive models in the future.